The "goldfish bowl": a qualitative study of the effects of heightened surveillance on people who use drugs in a rural and coastal Canadian setting - Geoff Bardwell; Manal Mansoor; Ashley Van Zwietering; Ellery Cleveland; Dan Snell; Thomas Kerr (BMC, 2022)
Abstract Background A growing body of research has focused on contextual factors that shape health and well-being of people who use drugs (PWUD). However, most of this research focuses on large cities and less is known about the effects of social and structural contexts on drug use and associated risks in rural Canadian settings. Therefore, we undertook this study to examine rural-specific contextual factors that affect the day-to-day experiences of PWUD. Methods Twenty-seven qualitative semi-structured interviews were conducted with PWUD in a rural and coastal setting in British Columbia, Canada. Participants had to be ≥ 19 years old, used illegal opioids and/or stimulants regularly, and lived in the qathet region. Interview transcripts were coded based on themes identified by the research team. Results Participants described progressive shifts in politics and culture in the qathet region while also identifying resource scarcity, homelessness, and changes in the drug supply, where illicit drug contents have become highly toxic and unpredictable. Participants discussed the qualities of a small community where everyone knows each other and there is a lack of privacy and confidentiality around drug use, which resulted in experiences of stigma, discrimination, and surveillance. Participants also reported rural-specific policing issues and experiences of surveillance on ferries when traveling to larger cities to purchase drugs. This led to significantly higher drug prices for PWUD due to the time dedication and criminalized risks associated with drug possession and trafficking. Conclusions Our findings illustrate the unique experiences faced by PWUD in a rural and coastal setting. The "goldfish bowl" effect in this rural community created heightened social and structural surveillance of PWUD, which led to a variety of negative consequences. There is a clear need for interventions to address the larger contextual drivers affecting people who use drugs in rural settings, including decriminalization and peer-led anti-stigma strategies, in order to improve the lives of PWUD.